EasyMIFs and SiteHound: a toolkit for the identification of ligand-binding sites in protein structures - Ghersi, Dario (Oxford University Press, 2009)
Summary: SiteHound uses Molecular Interaction Fields (MIFs) produced by EasyMIFs to identify protein structure regions that show a high propensity for interaction with ligands. The type of binding site identified depends on the probe atom used in the MIF calculation. The input to EasyMIFs is a PDB file of a protein structure; the output MIF serves as input to SiteHound, which in turn produces a list of putative binding sites. Extensive testing of SiteHound for the detection of binding sites for drug-like molecules and phosphorylated ligands has been carried out. Availability: EasyMIFs and SiteHound executables for Linux, Mac OS X, and MS Windows operating systems are freely available for download from http://sitehound.sanchezlab.org/download.html. Contact: roberto@sanchezlab.org or roberto.sanchez@mssm.edu Supplementary information: Supplementary data are available at Bioinformatics online.